Safety and efficacy of unidirectional barbed suture in mini-laparotomy myomectomy - Ming-Chao Huang; Ching-Hung Hsieh; Tsung-Hsien Su; Chih-Ping Chen; Tze-Yi Yang; Kung-Liahng Wang; Maw-Sheng Lee (Elsevier, 2013)
Objective: To estimate the safety and effectiveness of unidirectional knotless barbed suture compared to the traditional suture for repair of uterine wall defects through myomectomy via mini-laparotomy. Materials and Methods: This was a prospective clinical study performed by a single surgeon in a medical center. Sixty-eight women with symptomatic myoma were enrolled. Their uterine wall defects were repaired either by unidirectional knotless barbed suture (Group A) or by traditional suture (Group B). The surgical time, intraoperative blood loss, and number of myomas in the two groups were analyzed by two-sample t test. Results: Surgical time required from skin incision to complete closure was significantly lower in Group A than in Group B (50.2 ± 16.49 vs. 69.1 ± 25.33 min) (p = 0.0008). The intraoperative blood loss was also lower in Group A (mean, 260.9 mL; range, 20-850 mL) than in Group B (mean, 394.7 mL; range, 50-2200 mL) but not statistically significant. Conclusion: The unidirectional knotless barbed suture may facilitate the repair of uterine defects during mini-laparotomy myomectomy by significantly lowering operative time. It may also reduce the intraoperative blood loss.